Quercetagetin alleviates zearalenone-induced liver injury in rabbits through Keap1/Nrf2/ARE signaling pathway - Wu, Fengyang; Wang, Fengxia; Tang, Zhaohong; Yang, Xinyu; Liu, Yanhua; Zhao, Man; Liu, Shudong; Han, Shuaijuan; Zhang, Zhisheng; Chen, Baojiang (Frontiers in Pharmacology, 2023)
This study aimed to assess the alleviative effect of quercetagetin (QG) on zearalenone (ZEN)-induced liver injury in rabbits. Ninety 41-day-old healthy Hyla rabbits were randomly assigned into three groups, including a control (fed with basic diet), ZEN addition group (fed with basic diet+600 μg/kg ZEN), and ZEN+QG addition group (fed with basic diet+600 μg/kg ZEN+100 mg/kg QG), with 30 rabbits per group. The duration of the experiment was 28 days. The results revealed no significant differences in the average daily gain, average daily feed intake, the gain to feed ratio and the liver, kidney and spleen organ indexes (P>0.05) between the rabbits across the three groups. However, the sacculus rotundus index of the rabbits in the control group was significantly higher than that in the ZEN+QG group (P<0.05). The intake of ZEN-contaminated diet also significantly increased the activities or levels of alanine transaminase, alkaline phosphatase, total bile acid (TBA), total bilirubin, malondialdehyde, and interleukin-4 (IL-4) and enhanced the abundance of kelch-like ECH-associated protein 1 (Keap1), heat shock protein 70 (HSP70) and cysteine-aspartic acid protease-3 (Caspase-3) mRNA in the blood or liver tissue in ZEN group, compared to the control group (P<0.05). On the contrary, the activities or levels of immunoglobulin A, complement 3, total antioxidant capacity, glutathione peroxidase (GSH-Px), superoxide dismutase, interleukin-10, and the abundance of nuclear factor E2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) mRNA were significantly decreased (P<0.05). Supplementing the diet with QG still maintained significantly higher levels of TBA and IL-4, and the abundance of GSH-Px, HSP70, IL-4, and Caspase-3 mRNA in the blood and liver of rabbits in the ZEN+QG group than in the control group (P<0.05). At the same time, the other indicators were restored to levels in the control group (P>0.05). In conclusion, QG alleviated the ZEN-induced oxidative damage and liver injury caused by inflammatory reaction through the Keap1-Nrf2antioxidant response element (ARE) signal pathway, which protected the liver. This study revealed the